AMMI and GGE Biplot Analysis of Yield Stability and Adaptability of Elite Genotypes of Bread Wheat (Triticum aestivum L.) for Northern Hill Zone of India - Jeberson, M. S.; Kant, L.; Kishore, N.; Walia, D. P.; Singh, D. (International Journal of Bio-resource and Stress Management, 2017)
Bread wheat (Triticum aestivum L.) is a major food grain in India next to rice. Therefore, improving yield and yield stability is the primary objective of wheat breeding programmes in this country. The eleven wheat genotypes were evaluated under eight locations representing typical rainfed conditions of the North Hill Zone. The study based on AMMI and GGE biplot analysis methods to highlight the G×E interaction in multi-location trials and stratification of genotypes as per their adaptability for rainfed conditions of the northern hill zone. Combined ANOVA analysis showed highly significant differences (p<0.001) of 11 genotypes under rainfed conditions of North Hill Zone. Highly significant environments, genotypes and G×E interaction explained 81.4%, 2.3% and 15.7% of the total sum of squares, respectively (Table 2). The significant GE interaction sum of squares is further portioned into seven significant Interaction Principal Components Axes (IPCAs) and a residual term. The first four interaction principal component analysis (IPCA1, IPCA2, IPCA3 and IPCA4) explained 33.6%, 28.1%, 19.5% and 10.0% of the G×E interaction variation, respectively. Accordingly AMMI analysis for stability, genotypes G15, G3, G8, and G1 were shown to have a higher stability for yield than other genotypes. The GGE biplot analysis shown that the genotypes G10, G5, G7 and G1 were corner genotypes and suited to particular environments.